Effective asymmetric bioreduction of ethyl 4-chloro-3-oxobutanoate to ethyl (R)-4-chloro-3-hydroxybutanoate by recombinant E. coli CCZU-A13 in [Bmim]PF6-hydrolyzate media. (August 2016) - He, Yu-Cai; Tao, Zhi-Cheng; Di, Jun-Hua; Chen, Liang; Zhang, Lin-Bing; Zhang, Dan-Ping; Chong, Gang-Gang; Liu, Feng; Ding, Yun; Jiang, Chun-Xia; Ma, Cui-Luan
Graphical abstract: Highlights: Hydrolyzates promoted initial reaction rate and intracellular NADH content. Emulsifier OP-10 (20 mM) increased the initial reaction rate of whole cells. Hp-β-cyclodextrin (0.010 mol Hp-β-CD/mol COBE) increased the initial reaction rate. Effective biosynthesis of ( R )-CHBE (800 mM) was in [Bmim]PF6 -hydrolyzate media. Abstract: It was the first report that the concentrated hydrolyzates from the enzymatic hydrolysis of dilute NaOH (3 wt%)-soaking rice straw at 30 °C was used to form [Bmim]PF6 -hydrolyzate (50:50, v/v) media for bioconverting ethyl 4-chloro-3-oxobutanoate (COBE) into ethyl ( R )-4-chloro-3-hydroxybutanoate [( R )-CHBE] (>99% e.e. ) with recombinant E. coli CCZU-A13. Compared with pure glucose, the hydrolyzates could promote both initial reaction rate and the intracellular NADH content. Furthermore, emulsifier OP-10 (20 mM) was employed to improve the reductase activity. Moreover, Hp-β-cyclodextrin (0.01 mol Hp-β-cyclodextrin/mol COBE) was also added into this bioreaction system for enhancing the biosynthesis of ( R )-CHBE from COBE by E. coli CCZU-A13 whole-cells. The yield of ( R )-CHBE (>99% e.e. ) from 800 mM COBE was obtained at 100% in the [Bmim]PF6 -hydrolyzate (50:50, v/v) media by supplementation of OP-10 (20 mM) and Hp-β-CD (8 mM). In conclusion, an effective strategy for the biosynthesis of ( R )-CHBE was successfully demonstrated.